2003
DOI: 10.1590/s0103-84782003000600013
|View full text |Cite
|
Sign up to set email alerts
|

Polímero derivado de mamona acrescido de cálcio, associado ou não à medula óssea autógena na reparação de falhas ósseas

Abstract: Foram avaliados o processo de reparação tecidual e o comportamento do implante de polímero vegetal extraído do óleo de mamona acrescido de 40% de carbonato de sódio, associado ou não à impregnação com medula óssea autógena, em falhas ósseas experimentais em rádios de 30 coelhos e em sítio heterotópico em seis animais. Em quinze coelhos, a falha óssea no rádio direito foi preenchida por cilindros de polímero de mamona (grupo P) com dimensão semelhante à da falha; a falha no rádio direito dos outros coelhos rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
6
0
7
Order By: Relevance
“…In the present study, the animals of group 1 received castor oil polymer implants doped with SiO 2 and the animals of group 2 with BaTiO 3 , both replacing the equivalent to 10% of Del Carlo et al 16 observed the migration of osteoprogenitor cells invading the surface porous structure of castor oil polymer, followed by the direct bone deposition and concluded that castor oil polymer behaves like a passive framework that allows for progressive bone neoformation and osteoconduction, however, the biomaterial was not capable of promoting osteoinduction.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, the animals of group 1 received castor oil polymer implants doped with SiO 2 and the animals of group 2 with BaTiO 3 , both replacing the equivalent to 10% of Del Carlo et al 16 observed the migration of osteoprogenitor cells invading the surface porous structure of castor oil polymer, followed by the direct bone deposition and concluded that castor oil polymer behaves like a passive framework that allows for progressive bone neoformation and osteoconduction, however, the biomaterial was not capable of promoting osteoinduction.…”
Section: Discussionmentioning
confidence: 93%
“…Two factors encouraged the use of radiographs on the 7 th postoperative day: the studies conducted by Barros et al (2001b) andDel Carlo et al (2003), which observed early bone reconstruction, and the "gold standard" utilization. However, increased bone density was obtained in only 14.3% of the rabbits in the analyzed period, with no difference between CG and BMG.…”
Section: Discussionmentioning
confidence: 99%
“…Del Carlo et al (2004), em experimento utilizando polímero de mamona acrescido de cálcio, associado ou não com medula óssea em falhas criadas no rádio de coelhos, relataram que, aos 21dias de observação, o polímero implantado na falha apresentou-se envolto por uma camada de tecido fibroso, assim como observado no presente estudo aos 14 dias de observação. já se apresentava organizado e, assim como observado por Ignácio (1995), ele vai sendo gradativamente substituído por tecido ósseo imaturo.…”
Section: Methodsunclassified